2006
DOI: 10.1007/s00284-005-0138-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Natural Endophytic Rhizobia from Rice (Oryza sativa L.) Through rDNA PCR-RFLP and Sequence Analysis

Abstract: Three novel endophytic rhizobial strains (RRE3, RRE5, and RRE6) were isolated from naturally growing surface-sterilized rice roots. These isolates had the ability to nodulate common bean (Phaseolus vulgaris). Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and sequencing of 16S rDNA of these isolates revealed that RRE3 and RRE5 are phylogenetically very close to Burkholderia cepacia complex, whereas RRE6 has affinity with Rhizobium leguminosarum bv. phaseoli. Plant infection test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…These and other independent confirmations of worldwide, natural endophytic rhizobia-cereal associations and their benefit to the plant's growth physiology (Chaintreuil et al 2000;Dazzo et al 2000;Gutierrez-Zamora and Martinez-Romero 2001;Hilali et al 2001;Jha et al 2009;Lupway et al 2004;Mano and Morisaki 2008;Matiru and Dakora 2004;Mishra et al 2008;Peng et al 2008;Singh et al 2006;Singh et al 2009;Sun et al 2008;Tan et al 2001) have not lead to a technology that could be utilized directly by farmers, as positive plant-growth benefits obtained in lab, greenhouse and small experimental field plots still need meaningful "translational" research to prove the efficacy of biofertilizer inoculants under a variety of agricultural conditions, and successfully transfer those technologies to everyday use. The objective of this study was to conduct the translational research needed to assess the merit of applying this agricultural biotechnology in a large-scale rhizobial biofertilization program for rice under actual farming conditions, and by so doing, help the recent Emergency Rice Initiative achieve its important hunger-alleviating mission.…”
Section: Introductionmentioning
confidence: 75%
“…These and other independent confirmations of worldwide, natural endophytic rhizobia-cereal associations and their benefit to the plant's growth physiology (Chaintreuil et al 2000;Dazzo et al 2000;Gutierrez-Zamora and Martinez-Romero 2001;Hilali et al 2001;Jha et al 2009;Lupway et al 2004;Mano and Morisaki 2008;Matiru and Dakora 2004;Mishra et al 2008;Peng et al 2008;Singh et al 2006;Singh et al 2009;Sun et al 2008;Tan et al 2001) have not lead to a technology that could be utilized directly by farmers, as positive plant-growth benefits obtained in lab, greenhouse and small experimental field plots still need meaningful "translational" research to prove the efficacy of biofertilizer inoculants under a variety of agricultural conditions, and successfully transfer those technologies to everyday use. The objective of this study was to conduct the translational research needed to assess the merit of applying this agricultural biotechnology in a large-scale rhizobial biofertilization program for rice under actual farming conditions, and by so doing, help the recent Emergency Rice Initiative achieve its important hunger-alleviating mission.…”
Section: Introductionmentioning
confidence: 75%
“…Burkholderia cepacia showed the production of some pectolytic and cellulolytic enzymes (Singh et al 2006) that could possibly help them to get penetration in the intercellular spaces. The strains RRE-3 and RRE-5, used in the present study also produces a phytohormone IAA that plays an important role in colonization of bacteria by loosening of cell walls (Singh et al 2006). Fluorescent Burkholderia cepacia cells were observed on the surface of young root zones such as root hairs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is tremendous pressure on agriculturists worldwide to increase the Oryza sativa yield to meet growing consumption to feed a world population increasing day by day. However, unlike symbiotic plant-microbe interactions commonly observed in legumes, in several cereal crop plants including Oryza sativa, endophytic associations have been observed (Yanni et al 1997(Yanni et al , 2001Biswas et al 2000a, b;Chaintreuil et al 2000;Chi et al 2005;Singh et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inoculation of forage with rhizobial strains efficient in biological N fixation (BNF) can assist successive rice crops, either through plant residue decomposition or through an increase in N soil content. Furthermore, several studies have demonstrated that rhizobia and other symbiotic bacterial genera establish endophytic associations and promote rice growth (Yanni et al, 2001;Singh et al, 2006;Yanni and Dazzo, 2010).…”
Section: Introductionmentioning
confidence: 99%